Obtaining hybrids of cultivars and wild subspecies of cassava - Silva, Dreid de Cerqueira Silveira da; Martins, Márcio Lacerda Lopes; Santos, Ariana Silva; Santos, Vanderlei da Silva; Alves, Alfredo Augusto Cunha; Ledo, Carlos Alberto da Silva (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the crossability between cassava (Manihot esculenta subsp. esculenta) cultivars and the subspecies M. esculenta subsp. flabellifolia and M. esculenta subsp. peruviana. Plants from the BRS Jari, BRS Formosa, BRS Verdinha, and BGM 2050 (Equador 72) cultivars were crossed with the two subspecies. During flowering, at pre-anthesis, pistillate flowers were covered with a nylon bag and staminate flowers on the same inflorescence were emasculated. The staminate flowers were collected and placed in flasks previously labeled and sterilized with alcohol; some fresh flowers were stored at room temperature due to asynchronous flowering. The crosses were made between 10 a.m. and 2 p.m. After pollination, the flowers were covered again. Evaluations were made from the moment of pollination to the dehiscence of the fruit. Of the total flowers pollinated, 38% were fertilized, and 504 developed fruits and 816 produced seeds were observed. As a male parent, M. esculenta subsp. flabellifolia is more efficient in crosses with M. esculenta subsp. esculenta and may be recommend for controlled crosses. The crosses between the cassava cultivars and M. esculenta subsp. flabellifolia and M. esculenta subsp. peruviana produce viable seeds.